Pedagogical Based School Literacy Movement to Improve Reading Culture at SMAN 2 Klari - Yuyun Komalasari; Pupun Nuryani; Dian Penisiani (Nexus Publishing NXP, 2024)
The aim of this research is to describe the implementation of a pedagogy-based school literacy movement to improve reading culture at SMAN 2 Klari. The research method used in this research is qualitative descriptive research. Data was collected through in-depth interviews, observation, documentary research, and qualitative descriptive data analysis. Researchers analyze data through data reduction, data presentation, drawing conclusions and verification. The subjects of this research were students and teachers of SMAN 2 Klari. The results of the research show that: (1) the educational objectives of the GLS program need to be aligned with national educational objectives; (2) the role of educators as mentors and motivators in the GLS program and those in charge; and evaluators; (3) The role of students in the GLS project is not only seen as subjects, but as individuals who can develop and have potential; (4) The educational content of this GLS project is sustainable, flexible and comprehensive; (5) Educational facilities in the GLS project include habits, supervision and rewards; (6) Educational environment and supporting facilities to improve reading habits, namely libraries, digital technology and displays. The results of this research can be used to understand how implementing a learning-based school literacy movement can improve reading culture in schools.